Media Influence and Curiosity on Consumption Intention of Traditional Cake Products 'Iki Koué' in Jakarta - Ashifa Zulfa Faujiah; Novita Novita (Dinasti Publisher, 2024)
Jakarta is a metropolitan city that brings together various cultures. The activity of consuming food with diverse options has become a part of daily lifestyle, and social media plays an important role in this activity. Popular food trends can marginalize the existence of local cultures and traditional foods. Iki Koue is a traditional cake business that has been established since 2015. This research aims to identify the influence of media and curiosity due to social media marketing activities, which have the potential to affect and increase the intention to consume traditional food. The study employs a quantitative approach with non-probability sampling techniques, specifically purposive sampling, involving 100 respondents. Data were collected through an online survey and analyzed using IBM SPSS 25, employing multiple linear regression analysis, validity and reliability tests, classical assumption tests, as well as the Coefficient of Determination (R²) test, F test, and t-test. The results indicate that all hypotheses were proven to be positive and statistically significant. This finding shows that Media Influence and Curiosity can enhance the Consumption Intention for the traditional cakes from Iki Koue.